Implementasi Sistem Kenaikan Pangkat Otomatis Berbasis Online pada Kantor Regional VI Badan Kepegawaian Negara di Kota Medan - Savitri, Dessy; Arlina, Arlina (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
The implementation of a system of automatic promotion based online is one of the policies formulated by the state human resources agency in the letter to be no d-26 / 30 / v-99, explained one about the automatic promotion. This policy was made with the aim of accelerating, promotion because previously promotion often. The purpose of this study to described the made in automatic promotion system based on online and implemented in regional offices VI employment agency state in the city of Medan. This study using theory Van Meter van Horn. Descriptive methodes used is the method with a qualitative approach using theory Van Meter van Horn policy covering standards and objectives, resources, the in automatic promotion system based on online and implemented in relationship between organization (communication), characteristic of implementing agent, the social conditions, economic and political implementor and disposition. In this research data collection techniques used technique interview, observation and documentation . The result of the research indicated that the implementation of a system of automatic promotion based online at regional offices VI national civil service agency in the city of Medan was doing well, conforming to the standards and objectives set policy. Although the performance of the employee has been optimized with computerized there are still some obstacles in implementing this policy, because there are a lot of the implementing agency involved.